138 The influence of combined oncology and palliative care clinics (COPC) on hospital admissions. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Newman, Rachel; Hewitt, Abbie; Hines, Lucy; Jones, Molly; Green, Shauna
Abstract : Background: Current evidence suggests early palliative care involvement (PCI) alongside oncology care improves quality of life, planning and communication for advanced cancer patients. Little is known about the impact of PCI on hospital admissions. 800+consultations per year occur in Combined Oncology and Palliative Care clinics (COPC) at Royal Cornwall Hospital, each patient seen by the appropriate specialty consultant. Less COPC patients received radical or potentially curative treatment. This study examines the influence of COPC versus Standard Oncology (SO) clinics on hospital admissions. Methods: Fifty-five COPC patients with Breast, Prostate or Gastro-intestinal cancers were compared with fifty-eight attending SO (matched diagnoses). Number of non-elective hospital admissions and length of stay (LOS) were examined during a 12 month period. Results: In the COPC there were 45 admissions (LOS 4.3 days), and 70 admissions in the SO (LOS 5.6 days). The main reason for admission was a symptom/complication of diagnosis: COPC 84%; SO 86%. Of these complications of treatment were the reason in 10.5% of COPC admissions; but in 26.7% of SO admissions. 87% of COPC patients, and 81% of SO patients were discharged home. 45% COPC and 37% SO patients died within 12 months. Conclusions: Being reviewed in an integrated COPC compared to SO clinic appears to reduce the number and length of hospital admissions for advanced cancer patients. Spending less time in hospitals is important for patients, potentially increasing quality of life. Unsurprisingly, symptoms/complications of cancer were the main reason for admission, relating more often to complications of treatment in the SO group. More patients in the COPC group were discharged home. Reasons behind this were not explored, but may be due to planning discussions in clinics. Findings from this study may aid service development, but a larger cohort is needed to demonstrate statistical significance.